Interprofessional education in health professions education programmes in the Arab world: a scoping review protocol. Issue 11 (15th November 2022) - Waller, Susan; Östlundh, Linda; El-Awaisi, Alla
Abstract : Introduction: Interprofessional education is a relatively new addition to health professional education curricula in the Arab world. To understand current practice in this area, a scoping review will enable reporting of essential elements for the implementation of interprofessional education. The objective of this scoping review is to report on the implementation components, including presage, process and product, of interprofessional education in prelicensure health professions education programmes in the Arab world. Methods and analysis: A comprehensive and systematic search for literature will be conducted using eight electronic databases from their inception to September 2022. A presearch was devised in PubMed, Scopus and CINAHL using a combination of terms related to population, context and concept. The Covidence Systematic Review tool will be used for blind screening, selection and conflict resolution. Data will be presented in tabular format and as a narrative synthesis and will include elements that support the implementation of interprofessional education. This review will be presented according to the Joanna Briggs Institute methodology. Studies conducted with students and/or faculty in prelicensure health professions education programmes will be included. The concept to be explored is interprofessional education. The context is the region commonly known as the Arab world, which includes 18 countries, sharing many common social and cultural traditions and where Arabic is the first language. Excluded will be studies conducted on collaborative practice of health professionals and postlicensure interprofessional education. Ethics and dissemination: No ethical approval was required. Findings will be disseminated in conference presentations and peer-reviewed articles.